Characterization and clinical outcomes of outpatients with subacute or chronic post COVID-19 cough: a real-world study - Chun Yao; Dongliang Cheng; Wenhong Yang; Yun Guo; Tong Zhou (PeerJ)
Background Limited research exists on the features and management of post-COVID cough. This real-world study investigates outpatients with subacute or chronic post-COVID cough, aiming to delineate characteristics and regimen responses within the population. Method We enrolled eligible patients from our outpatient unit between August 2023 and February 2024. Comprehensive clinical data, prescriptions, and patient-reported cough severity were collected during the primary visit and subsequent follow-ups. Result A total of 141 patients, aged: 42 ± 14 years old, were included, with 70% being female. The median cough duration was 8 weeks (interquartile range 4–12 weeks). Sixty percent presented with a dry cough, while the rest had coughs with phlegm. Over half reported abnormal laryngeal sensations (54%). Twenty-one percent coughed during the day, while 32% coughed constantly, and 48% experienced nocturnal episodes. Compound methoxyphenamine capsules were the most prescribed, but our study found ICS/LABA to be the most effective, followed by compound methoxyphenamine capsules, montelukast, and Chinese patent drugs. Conclusion Females exhibit a higher prevalence of post-COVID cough, and our study recommends ICS/LABA as the preferred treatment. These findings warrant validation through larger, prospectively designed studies.